Risk Factors to Growth Retardation in Major Thalassemia (Majalah Kedokteran Bandung, 2011)
The increasing in the life span of patients with major thalassemia should be followed by increased quality of life. There are factors which can affect growth retardation in these patients. The aim of this study was to find out the risk factors for growth retardation in patients with major thalassemia. An analytical study with cross-sectional design was conducted at Pediatric Thalassemia Clinics of Dr.Hasan Sadikin Hospital, Bandung, in June to July 2006. The subjects of this study were patients with major thalassemia. Inclusion criteria’s were age under 14 years old, had no chronic diseases like tuberculosis, cerebral palsy with complete medical records. Risk factors were the timing of diagnosis, initial and dose of deferoxamine, volume of transfused blood, mean pretransfusion hemoglobin level, family income, and age. Antropometric measurement indices were used to assess the growth which expressed in Z score. Growth evaluated based on height/age (H/A) and growth retardation if H/A